Smart grids investigation and analysis in terms of cost benefits - Rubini, B; Shanmugasundaram, N; Pradeepkumar, S (International Journal of Engineering and Technology, 2018)
Currently, different advanced technologies are implemented in power networks, with aim to improve power quality and reliability of grid operation. Naturally, Distribution Automation and Management Systems (DAMS), Smart power equipment, Advanced Metering Structure, Distributed Energy Resources and/or systems Demand Response are implemented in electricity distribution networks. Smart Grid Solutions coordinate different advanced technologies in an efficient energy management system. Outline Smart Grid Solutions, with investments of estimation, possible benefits and operation costs, is presented in this article, with estimation of cost-effectiveness in a lifetime of particular systems.Â